2013
DOI: 10.1016/j.exppara.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Gene silencing in root lesion nematodes (Pratylenchus spp.) significantly reduces reproduction in a plant host

Abstract: Accepted ManuscriptThis is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. hours in soaking solutions cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 40 publications
3
92
0
1
Order By: Relevance
“…An example of such phenotype in PPNs is the silencing of two genes involved in movement, pat-10 and unc-87 , in J2s of P. thornei which reduced reproduction by 77–81% on carrot mini discs. The phenotypic effect after feeding dsRNA to these nematodes was abnormal behaviour including twitching, slow movement, repeated banging of the head against the body and loss of orientation [72].…”
Section: Discussionmentioning
confidence: 99%
“…An example of such phenotype in PPNs is the silencing of two genes involved in movement, pat-10 and unc-87 , in J2s of P. thornei which reduced reproduction by 77–81% on carrot mini discs. The phenotypic effect after feeding dsRNA to these nematodes was abnormal behaviour including twitching, slow movement, repeated banging of the head against the body and loss of orientation [72].…”
Section: Discussionmentioning
confidence: 99%
“…When treated nematodes were transferred to carrot minidiscs for 5 weeks, there was a significant reduction in reproduction of 77-81%: Moreover, for these two genes, dsRNA derived from either nematode species silenced the corresponding gene in both species. This observation suggests that cross-species control of nematodes via RNAi is possible (106). RNAi has also been demonstrated for a transcript with a SPRY domain and calreticulin of P. zeae (32) and endoglucanases of P. vulnus (26).…”
Section: Gene Silencing In Root Lesion Nematodesmentioning
confidence: 85%
“…The first papers that demonstrated that RNAi could also be applied to RLNs were the effective silencing of two movement-related genes, calponin (unc-87) and troponin C ( pat-10) of P. coffeae (102) and P. thornei (106): RNAi results have since been substantiated for P. vulnus (26), P. zeae (32), and P. penetrans (112). When mixed stages of P. thornei or P. zeae were soaked for 16 h in dsRNA to unc-87 or pat-10, there was a significant reduction in expression of these target genes, and the treatment resulted in paralysis and uncoordinated movements in both species.…”
Section: Gene Silencing In Root Lesion Nematodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, assisting in the identification of the key genes involved in parasitism, the genomic and EST sequences so generated could also provide clue to researchers to pinpoint appropriate target genes for RNAi experiments. Recently a report has been published by Tan et al, (2013) where they described the dsRNA mediated gene silencing in two important RLN species P. thornei and P.zeae. Artificial feeding silenced two important genes, calponin and troponin C, essential for nematode structural integrity and proper muscle contraction.…”
Section: Introductionmentioning
confidence: 99%